Stimulation of Baroresponsive Parts of the Nucleus of the Solitary Tract Produces Nitric Oxide-mediated Choroidal Vasodilation in Rat Eye - Li, Chunyan; Fitzgerald, Malinda E. C.; Del Mar, Nobel; Reiner, Anton (Frontiers in Neuroanatomy, 2016)
Preganglionic parasympathetic neurons of the ventromedial part of the superior salivatory nucleus (SSN) mediate vasodilation of orbital and choroidal blood vessels, via their projection to the nitrergic pterygopalatine ganglion (PPG) neurons that innervate these vessels. We recently showed that the baroresponsive part of the nucleus of the solitary tract (NTS) innervates choroidal control parasympathetic preganglionic neurons of SSN in rats. As this projection provides a means by which blood pressure (BP) signals may modulate choroidal blood flow (ChBF), we investigated if activation of baroresponsive NTS evokes ChBF increases in rat eye, using Laser Doppler Flowmetry (LDF) to measure ChBF transclerally. We found that electrical activation of ipsilateral baroresponsive NTS and its efferent fiber pathway to choroidal SSN increased mean ChBF by about 40–80% above baseline, depending on current level. The ChBF responses obtained with stimulation of baroresponsive NTS were driven by increases in both choroidal blood volume (ChBVol; i.e., vasodilation) and choroidal blood velocity (ChBVel; possibly due to orbital vessel dilation). Stimulation of baroresponsive NTS, by contrast, yielded no significant mean increases in systemic arterial blood pressure (ABP). We further found that the increases in ChBF with NTS stimulation were significantly reduced by administration of the neuronal nitric oxide (NO) synthase inhibitor Nω-propyl-l-arginine (NPA), thus implicating nitrergic PPG terminals in the NTS-elicited ChBF increases. Our results show that the NTS neurons projecting to choroidal SSN do mediate increase in ChBF, and thus suggest a role of baroresponsive NTS in the BP-dependent regulation of ChBF.